One-step purification and concentration of DNA in porous membranes for point-of-care applications1. Issue 12 (21st June 2015) - Byrnes, S. A.; Bishop, J. D.; Lafleur, L.; Buser, J. R.; Lutz, B.; Yager, P.
<x xml:space="preserve">Abstract</x> Nucleic acid purification in porous membranes at the point-of-care from complex samples including nasal matrix and blood using a single-user step.